Environmentally benign catalytic hydroformylation-oxidation route for naproxen synthesis - Rajurkar, Kalpendra B.; Tonde, Sunil S.; Didgikar, Mahesh R.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2007)
Hydroformylation of 6-methoxy-2-vinylnaphthalene (MVN), using homogeneous Rh(CO)acac) as a catalyst and a chelating bidentate ligand (1,2-bis-(diphenylphosphino) ethane, dppe), followed by oxidation of the product (2-(6-methoxynaphthyl) propanal, 2-MNP) has been studied as an alternative route for the synthesis Of D,L-naproxen. The feasibility of the MVN hydroformylation route has been demonstrated, and a detailed study has been reported on the key hydroformylation step. The roles of the catalyst, ligands, and solvents, as well as the effect of reaction conditions on the reaction rate and regioselectivity of the product 2-MNP, have been investigated. With Rh(CO)2(acac) as a catalyst and dppe as a ligand, > 98% selectivity to 2-MNP (an important precursor to D,L-naproxen) has been achieved. A possible mechanism to explain the variation in regioselectivity with Rh(CO)(2)(acac) as a catalyst and dppe as a ligand has been discussed. The kinetics of the hydroformylation step has been investigated and a rate equation has been proposed. The second step in the proposed route for naproxen-the oxidation of 2-MNP to 2-(6-methoxynaphthyl) propanoic acid (2-MNPA, or naproxen) - has been studied using Na2WO4 as a catalyst and tetrabutyl ammonium hydrogen sulfate (TBAHS) as the phase-transfer catalyst with H2O2 as the oxidant for the first time. Screening of the catalysts that consisted of the early transition metals, such as salts of tungsten, vanadium, and molybdenum showed that Na2WO4 gives the best performance for the oxidation step with > 80% selectivity to 2-(6-methoxynaphthyl)propanoic acid (2-MNPA/naproxen). This study would be valuable in developing a new environmentally benign route for naproxen synthesis.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007

Immobilized palladium nanoparticles catalyzed oxidative carbonylation of amines - Didgikar, Mahesh R.; Roy, Debdut; Gupte, Sunil P.; Joshi, Sunil S.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2010)
Catalytic application of immobilized palladium nanoparticles for synthesis or ureas by oxidative carbonylation of amines has been investigated. This is the first report oil oxidative carbonylation of amines to ureas using immobilized palladium nanoparticles catalyst. The palladium nanoparticles were immobilized on a NaY zeolite support through 3-aminopropyl-trimethoxysilane (APTS) as anchoring agent. The [Pd]-APTS-Y catalyst along with NaI promoter showed high conversion and selectivity to the desired urea products over several amine compounds including ail example of an aliphatic amine precursor even at 333 K. The immobilized catalyst was easily separated and recycled several times without any loss of activity. The role of different solvents, iodide promoters, iodide to Pd ratio, concentration of substrates, and temperature on the overall yield of the reaction was also investigated.
Joint 7th International Symposium on Catalysis in Multiphase Reactors (CAMURE-7)/6th International Symposium on Multifunctional Reactors (ISMR-6), Montreal, CANADA, AUG 23-26, 2009

Oxidative carbonylation of amine using water-soluble palladium catalysts in biphasic media - Didgikar, Mahesh R.; Joshi, Sunil S.; Gupte, Sunil P.; Diwakar, Makarand M.; Deshpande, Raj Madhukar; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A-Chemical, 2011)
Application of water-soluble palladium catalysts for oxidative carbonylation of aniline to N,N' diphenyl urea (DPU) has been reported. The water-soluble palladium catalysts prepared from sulfonated N-containing ligands were found to be highly stable under reaction conditions and easily recyclable due to insoluble urea product in the reaction medium. This is in contrast to the sulfonated phosphine ligands, which are vulnerable to oxidation under reaction conditions, showing poor activity and stability. Commercially available as well as laboratory synthesized ligands were used for preparing water-soluble palladium catalysts, for oxidative carbonylation of aniline. The best activity was obtained for Pd complex with disodium 2,2'-bipyridine-4,4'-disulfonate (Bipy-DS) ligand. Under optimized conditions Pd(BipyDS)Pd(OAc)(2) catalyst gave TOF of similar to 210h(-1) with aniline conversion of similar to 97% with similar to 91% selectivity for N.N'-diphenyl urea. It was found that the catalyst was easily reusable up to five times, with negligible loss in the catalytic activity. The effect of reaction parameters was investigated and a plausible reaction mechanism has been proposed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amine; Biphasic catalysis; Carbonylation; Urea; Water-soluble palladium catalyst